Outcome of isolated posterior cruciate ligament reconstruction at mean 6.3-year follow up: a consecutive case series. Issue 1 (2nd January 2019) - Rauck, Ryan C.; Nwachukwu, Benedict U.; Allen, Answorth A.; Warren, Russell F.; Altchek, David W.; Williams, Riley J.
ABSTRACT: Objectives : There is a paucity of reporting on surgical outcomes of isolated posterior cruciate ligament reconstruction (PCLR). We hypothesize that isolated PCL injuries failing nonoperative treatment achieve good outcomes and are able to return to sport following PCLR. Methods : A retrospective analysis was performed to identify patients with isolated PCL injuries that underwent reconstruction between 2001 and 2014. Patients with multi-ligamentous injury or another concomitant knee pathology were excluded. Medical records were reviewed for demographic, clinical and operative data. Patients were contacted for administration of a telephone-based questionnaire which included the International Knee Documentation Committee (IKDC) Subjective Knee Evaluation form, Lysholm-Tegner scales, Marx activity scale (MAS), return to sport status, and patient satisfaction instruments. Results : A total of 15 isolated PCL reconstructions in 14 patients with a mean age of 27.5 years (range 17–43) met the study inclusion criteria; mean follow up was 6.3 years (range 1.4–15.2). Pre-operatively, the primary complaint was knee instability in all patients; on physical examination, lack of a firm end point during posterior drawer testing was found in 93% (14/15) of the knees. In total, 12 of 15 knees underwent transtibial, single-bundle PCLR and three of 15 underwent tibial inlay, double bundle PCLR. Graft types included: quadriceps autograft (7/15), Achilles allograft (6/15), and hamstring autograft (2/15). There were no graft failures in our patient cohort. At most recent follow up the mean scores respectively on the IKDC form, Lysholm-Tegner scales and MAS were (standard deviation): 77.3 (16.5), 83.1 (17.9), 6.13 (2.6), and 7.1 (6.0). All fourteen patients were athletes prior to their injury and 79% (11/14) returned to sport and overall patient satisfaction was 9.2/10. Conclusions : Isolated PCLR provides good outcomes at mean medium-term follow up with restoration of function, high rate of return to sport and overall patient satisfaction.